Evaluation of Life Cycle Cost (LCC) of Flexible Pavement and Rigid Pavement on Bhayangkara Road Section, Samarinda City - Hendra Gunawa; Risma Marleno; Retno Hastijanti (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2026)
The development of irrigation infrastructure is an important factor in supporting the agricultural sector, particularly in areas that rely on irrigation systems to improve agricultural productivity. One of the main challenges in implementing irrigation projects is selecting the appropriate construction method to achieve time This research evaluates the life cycle cost (LCC) of flexible and rigid pavement alternatives for Jalan Bhayangkara, Samarinda, to determine the most economical pavement type over the design life. A quantitative LCC analysis based on Net Present Value (NPV) at a 6% discount rate was performed for a 20-year planning period. Cost components included initial construction, routine maintenance, periodic maintenance, rehabilitation, and salvage value. Data sources comprised field surveys, technical documents, maintenance records, and budget estimates. The total LCC for flexible pavement was calculated at IDR 11.19 billion, while rigid pavement yielded a lower total LCC of IDR 10.19 billion. The cost difference of IDR 999.76 million (approximately 8.9%) indicates that rigid pavement is more cost-effective over the analysis period, primarily due to lower maintenance demands and higher structural resilience in the wet, heavy-traffic conditions typical of Samarinda. Consequently, rigid pavement is recommended as the more economical and sustainable option for Jalan Bhayangkara when considering long-term lifecycle costs.